Legal Protection Of Trade Secret Owners Through Non Disclosure Agreements To Guarantee Investment Security - Afif Khalid; Yamani Naufal (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The protection of trade secrets against non-disclosure agreements is increasingly necessary in every cooperation agreement as a form of intellectual property protection. The purpose of this research is to know and understand the urgency of the inclusion of confidential information in the clause of the cooperation agreement so that it is fundamental to the principle of pacta sunt servanda. This research uses an analytical approach method to examine research materials through analysis of legal materials using normative legal research methods (Legal Research) In the protection of trade secrets, it also has a consequential impact on the abuse of the authority of the trade secret agreement contract because it has the nature of information that must be protected and not informed anywhere.